2017
DOI: 10.1007/s41809-017-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Lace your mind: the impact of an extra-curricular activity on enantiomorphy

Abstract: The present study examined whether a beneficial effect on enantiomorphy (namely, the ability to discriminate lateral mirror images) can be gained by practicing extra-curricular activities that require making mirror-image discrimination on nonsymbolic materials. In particular, we examined whether lacemaking triggers enantiomorphy in unschooled illiterate adult women. To this aim, two groups of illiterate women were presented with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…We point out that mirror-image discrimination is not specific to the Latin alphabet, literacy, or visual training. Illiterate adults who are lacemakers, and hence, trained in explicit mirror-image discrimination of visuospatial patterns, have as good mirror-image discrimination as exilliterate adults (and better than illiterate who are not lace-makers: Kolinsky & Verhaeghe, 2017). Moreover, congenital-blind readers of Braille (a tactile script with more mirrored graphs than Latin alphabet) have as good explicit mirror-image discrimination as Latin-alphabet readers and both groups show mirror costs (de Heering et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We point out that mirror-image discrimination is not specific to the Latin alphabet, literacy, or visual training. Illiterate adults who are lacemakers, and hence, trained in explicit mirror-image discrimination of visuospatial patterns, have as good mirror-image discrimination as exilliterate adults (and better than illiterate who are not lace-makers: Kolinsky & Verhaeghe, 2017). Moreover, congenital-blind readers of Braille (a tactile script with more mirrored graphs than Latin alphabet) have as good explicit mirror-image discrimination as Latin-alphabet readers and both groups show mirror costs (de Heering et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Mirror invariance is a robust perceptual phenomenon, mostly in people without reading skills: preliterate children and illiterate adults (e. g., Fernandes, Coelho, Lima, & Castro, 2018;Gibson, Pick, Osser, & Gibson, 1962;Kolinsky et al, 2011). It is not about post-perceptual or memory processes (Corballis, 2018): For non-readers, mirror-image discrimination is hard (across-task: e.g., visual search, same-different matching, card sorting; Fernandes et al, 2018;Fernandes, Leite, & Kolinsky, 2016;Kolinsky et al, 2011), more in simultaneous than in sequential presentation (Kolinsky et al, 2011;Kolinsky & Verhaeghe, 2017). It is neither because orientation is a hard dimension: Non-readers can discriminate plane rotations (i.e., rotation in the image-plane of, e.g., 180…”
Section: Introductionmentioning
confidence: 99%
“…Here we showed that the spatial discriminability hypothesis predicts the pattern of FoR use across axes, but this account also has the potential to explain variation in FoR use over development, between individuals, and across cultures. Indeed, spatial discrimination abilities vary at all of these levels (Kolinsky & Verhaeghe, 2017;Cox & Richardson, 1985; and some evidence suggests that they correlate with FoR use. For example, whereas adults from industrialized cultures are practiced in left-right discrimination and tend to prefer egocentric space, adults in some unindustrialized groups (where left-right distinctions may be less important) show relatively low left-right discrimination abilities and tend to prefer allocentric FoRs on the lateral axis (Pederson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond reading and writing, other cultural practices predict differences in spatial discrimination abilities. For example, among illiterate adults in Portugal, left-right discrimination was significantly better among those who practiced lacemaking, which involves making mirror images of the same pattern, than those who did not (Kolinsky & Verhaeghe, 2017). On the spatial discrimination hypothesis, any experience that encourages a person to distinguish the poles of a given spatial continuum (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation